2023
DOI: 10.1093/nar/gkac1250
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNP C tetramer binds to CBC on mRNA and impedes PHAX recruitment for the classification of RNA polymerase II transcripts

Abstract: In eukaryotic cells, various classes of RNAs are exported to the cytoplasm by class-specific factors. Accumulating evidence has shown that export factors affect the fate of RNA, demonstrating the importance of proper RNA classification upon export. We previously reported that RNA polymerase II transcripts were classified after synthesis depending on their length, and identified heterogeneous nuclear ribonucleoprotein (hnRNP) C as the key classification factor. HnRNP C inhibits the recruitment of PHAX, an adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…A minimal region, PHAX 103-327 , is required for full binding (Schulze et al, 2018), which includes the PHAX non-specific RNA-binding domain (Mourao et al, 2010; Segref et al, 2001). PHAX may initially bind to a wide-range of transcripts (Giacometti et al, 2017) but is thought to be displaced by hnRNP-C on RNAs, such as mRNAs, with long enough (> 200 nts) unstructured 5’ regions (Dantsuji et al, 2023; McCloskey et al, 2012). It has been shown that PHAX binding to CBC is incompatible with the binding of NELF-E (Schulze and Cusack, 2017) and ZC3H18 (Giacometti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A minimal region, PHAX 103-327 , is required for full binding (Schulze et al, 2018), which includes the PHAX non-specific RNA-binding domain (Mourao et al, 2010; Segref et al, 2001). PHAX may initially bind to a wide-range of transcripts (Giacometti et al, 2017) but is thought to be displaced by hnRNP-C on RNAs, such as mRNAs, with long enough (> 200 nts) unstructured 5’ regions (Dantsuji et al, 2023; McCloskey et al, 2012). It has been shown that PHAX binding to CBC is incompatible with the binding of NELF-E (Schulze and Cusack, 2017) and ZC3H18 (Giacometti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian TGF-β consists of three isoforms: TGF-β1, TGF-β2 and TGF-β3, and all of them have been reported to induce EndMT in human endothelial cells (Ciavarella et al, 2021;Hong et al, 2020;Nasim et al, 2023). HNRPC is a nuclear-restricted RNA-binding protein involved in mRNA stability, splicing, export and translation (Dantsuji et al, 2023;L. Mo et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, the tetramer sorts the transcripts into two RNA categories: mRNA or uridine-rich small nuclear RNA (U snRNA). Further mechanistic studies proved that the hnRNP-C tetramer binds the cap-binding complex (CBC) on mRNA and blocks PHAX (an adaptor protein for splicosomal U snRNA output) recruitment for the classification of RNA polymerase II transcripts, so as to direct these RNAs to the mRNA nuclear export pathway [ 59 ]. This discovery of the hnRNP C tetramer for length-specific RNA classification contributes to a deeper understanding of RNA biogenesis and provides potential strategies for future disease treatments.…”
Section: Cellular Mrna Nuclear Exportmentioning
confidence: 99%